Pendampingan Kegiatan Lesson Study for Learning Community (LSLC) Guru Matematika MTS-MA-SMK Pondok Pesantren Darussholihin NW Kalijaga Lombok Timur - Sripatmi Sripatmi; Ratih Ayu Apsari; Nourma Pramestie Wulandari; Ulfa Lu’luilmaknun; Nilza Humaira Salsabila (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
As an effort to develop the teaching profession, Lesson Study for Learning Community (LSLC) emphasizes the importance of collaborative and continuous learning assessment based on the principles of collegiality and mutual learning to build a learning community. Based on discussions with the head of Darussholihin Islamic Boarding School (Ponpes) NW Kalijaga, East Lombok, principals of MTs-SMP, MA-SMA, and Vocational Schools fostered by Ponpes Darussholihin NW Kalijaga, it was revealed that: mathematics is one of the subjects that most students are less interested in. MTs-SMP, MA-SMA, SMK fostered by Ponpes Darussholihin NW Kalijaga, as well as most mathematics teachers still have difficulty planning and implementing learning strategies that can guide students in finding mathematical concepts, principles, and problem solving. To solve these problems, assistance is needed, through LSLC activities for school mathematics teachers at Ponpes Darussholihin NW Kalijaga, in order to resolve problems related to the implementation of mathematics learning. This service activity is carried out by utilizing several methods, namely: lectures, questions and answers, discussions, and providing assistance when mathematics teachers carry out the LSLC steps, including Plan, Do, See, and Re-design activities. Through mentoring activities carried out from September 18 to October 2, 2021, it was concluded that mentoring activities could: i) improve the understanding and skills of Mathematics teachers in schools at Ponpes Darussholihin NW Kalijaga in designing (plan), implementing (do), reflecting (see), and re-design of learning as regulated in the 2013 curriculum; ii) increasing collegiality among mathematics teachers at the Darussholihin Islamic Boarding School's fostered schools, NW Kalijaga.